Information national policy: an overview - Khalifa, Mahmoud (Cybrarians Journal, 2023)
Library and Information Policy (LIP) remains essential yet underutilized, despite decades of discourse. This paper reviews its evolution and current status, highlighting the need for a distinct focus on libraries within national information frameworks. Analyzing policy issues and establishment processes, it identifies gaps and emphasizes the importance of context-specific approaches. Global efforts are examined, showcasing diverse approaches. The paper advocates for renewed attention to comprehensive LIP frameworks that recognize libraries' unique roles and address contemporary challenges.